(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This research explores the concept of soft power, its mechanisms, and its influence on international relations. It begins by defining power as the ability to influence decisions and actions, distinguishing between hard power and soft power. The study emphasizes Joseph Nye’s concept of soft power, which operates through attraction rather than coercion, and its significance in the globalized era. It further discusses the role of culture, ideology, and foreign policy in soft power, citing historical examples such as the cultural influence of Ancient Greece and the Soviet Union’s ideological leadership. The research highlights how soft power manifests in today’s world, from media and education to cultural diplomacy and international relations. A specific focus is placed on Uzbekistan’s cultural diplomacy as a tool for enhancing its soft power, with examples of prominent figures like Kato Kyudzo and Ikuo Hirayama, who contributed to Uzbek-Japanese relations. The paper concludes by discussing the strategic use of soft power for Uzbekistan, considering its cultural, historical, and religious assets, and the potential benefits of enhancing its international image through cultural exchanges, educational initiatives, and diplomatic efforts.